Botswana : Technical Assistance Report-Report on Price Statistics Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses the report on Botswana by technical assistance mission conducted in response to a request from Statistics Botswana (SB) to assist with updating the consumer price index (CPI) and to review progress with the development of the producer price index (PPI). SB has compiled a draft PPI for mining and quarrying and plan to disseminate these data in September 2019. Further work to expand PPI coverage has been slower than anticipated for a number of reasons, including: data from the 2017 census of economic activity are still not available; resources diverted to support updating the CPI; and issues with the collection of price data. Improvements were identified in the compilation of the mining PPI. The report highlights that whilst the staff clearly show the capability for developing price indexes, they are limited by the amount of resource available with which to develop and disseminate indexes. SB management should carefully review the staff and budgetary resources needed to continue a program of development for PPI and ongoing improvement of the CPI.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet